2021
DOI: 10.1038/s41467-021-25585-5
|View full text |Cite
|
Sign up to set email alerts
|

Pericyte-derived fibrotic scarring is conserved across diverse central nervous system lesions

Abstract: Fibrotic scar tissue limits central nervous system regeneration in adult mammals. The extent of fibrotic tissue generation and distribution of stromal cells across different lesions in the brain and spinal cord has not been systematically investigated in mice and humans. Furthermore, it is unknown whether scar-forming stromal cells have the same origin throughout the central nervous system and in different types of lesions. In the current study, we compared fibrotic scarring in human pathological tissue and co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
106
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(114 citation statements)
references
References 59 publications
7
106
1
Order By: Relevance
“…More importantly, reduced ischemia-induced expression of PDGFR β in the lesion core has been found to correlate with an enlargement of infarct volume after MCAO 56 and stromal PDGFR β + pericytes have been reported not to contribute to ECM production in the fibrotic lesion after stroke 57 . The latter is however in stark contrast to the lineage tracing studies of type A pericytes 50 , where type A pericytes were shown to give rise to nearly the entire fibrotic scar in the lesion core after cortical MCAO, a region of the fibrotic scar that appeared unaffected by imatinib treatment in our analyses. Nevertheless, this highlights a heterogeneity of the fibrotic scar, where it seems that reducing the PDGFRα + myofibroblast portion is beneficial, whereas tampering with the fibrotic core portion of the scar might be detrimental, although this requires further investigation.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…More importantly, reduced ischemia-induced expression of PDGFR β in the lesion core has been found to correlate with an enlargement of infarct volume after MCAO 56 and stromal PDGFR β + pericytes have been reported not to contribute to ECM production in the fibrotic lesion after stroke 57 . The latter is however in stark contrast to the lineage tracing studies of type A pericytes 50 , where type A pericytes were shown to give rise to nearly the entire fibrotic scar in the lesion core after cortical MCAO, a region of the fibrotic scar that appeared unaffected by imatinib treatment in our analyses. Nevertheless, this highlights a heterogeneity of the fibrotic scar, where it seems that reducing the PDGFRα + myofibroblast portion is beneficial, whereas tampering with the fibrotic core portion of the scar might be detrimental, although this requires further investigation.…”
Section: Discussioncontrasting
confidence: 98%
“…Contrary to PDGFRα however, PDGFR β is also expressed in vascular mural cells, both in pericytes distributed along the capillaries and vSMC 33 . Also, during ischemic stroke, expression of PDGFR β is highly upregulated throughout the ischemic core region, and not selectively only at the rim of the astroglia scar 50, 55 . More importantly, reduced ischemia-induced expression of PDGFR β in the lesion core has been found to correlate with an enlargement of infarct volume after MCAO 56 and stromal PDGFR β + pericytes have been reported not to contribute to ECM production in the fibrotic lesion after stroke 57 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It appears, that further studies will be necessary to understand the mechanisms responsible of this distinct lesion scar evolution overtime. In a broader perspective, it has been recently shown that this brotic scar is present in different central nervous system lesions in mice such as traumatic brain or spinal cord injuries but also after demyelinating or ischemic lesion models 24 . It could be also interesting to demonstrate if this brotic scar is present throughout species after CNS lesions.…”
Section: Discussionmentioning
confidence: 99%